Early invasive fungal infections and colonization in patients with cirrhosis admitted to the intensive care unit. (February 2016) - Theocharidou, E.; Agarwal, B.; Jeffrey, G.; Jalan, R.; Harrison, D.; Burroughs, A.K.; Kibbler, C.C.
Abstract: Bacterial infections in cirrhosis are common and associated with increased mortality, but little is known about fungal infections. The aim of this study, a sub-analysis of the Fungal Infection Risk Evaluation study, was to assess the incidence and implications of early invasive fungal disease (IFD) in patients with cirrhosis admitted to intensive care units (ICU). Clinical and laboratory parameters collected in the first 3 days of ICU stay for 782 patients with cirrhosis and/or portal hypertension were analysed and compared with those of 273 patients with very severe cardiovascular disease (CVD). The CVD patients had more co-morbidities and higher APACHE II scores. The overall incidence of IFD was similar in the two groups, but the incidence of IFD in ICU was higher in liver patients (1% versus 0.4%; p 0.025) as was fungal colonization (23.8% versus 13.9%; p 0.001). The ICU and in-hospital mortality, and length of stay were similar in the two groups. A higher proportion of liver patients received antifungal therapy (19.2% versus 7%; p <0.0005). There was no difference in mortality between colonized patients who received antifungal therapy and colonized patients who did not. The incidence of IFD in patients with cirrhosis in ICU is higher compared with another high-risk group, although it is still very low. This risk might be higher in patients with advanced liver disease admitted with acute-on-chronic liver failure, and this should be investigated further. Our data do not support prophylactic use of antifungal therapy in cirrhosis.